SUBORDINATOR RELASI TEMPORAL DALAM KALIMAT MAJEMUK BERTINGKAT - Andi Haris Prabawa (Kajian Linguistik dan Sastra, 2015)
The study describes subordinators indicating temporal relations of equivalence and sequence in which their existence in compound-complex sentences are obligatory. The distribution method and its five techniques (Immediate Constituent, deletion, permutation, substitution, and expansion) are used to identify the types and distribution of the subordinators within the Indonesian sentences. The result shows that subordinators indicating equivalence of temporal relations are saat, ketika, waktu, sewaktu, kala, tatkala, selama, and selagi. Meanwhile, subordinators indicating sequence of temporal relations are begitu, usai, sesuai, sesudah, selepas, and sehabis. The distribution of the two kinds of subordinators in the cimpound-complex sentences vary; they can be placed initially, medially after the main clause, and after subject of the main clause.